GREEN CHEMISTRY APPROACHES IN THE EXTRACTION OF BIOACTIVE COMPOUNDS FROM FOOD SOURCES (International Journal of Food and Nutritional Sciences, 2021)
Green chemistry principles offer sustainable and eco-friendly methods for the extraction of bioactive compounds from food sources. Traditional extraction methods often involve hazardous solvents and high energy consumption, raising environmental and health concerns. This paper reviews green chemistry approaches to bioactive compound extraction, emphasizing the reduction of harmful substances and energy use. The study explores various green techniques, including supercritical fluid extraction (SFE), microwave-assisted extraction (MAE), ultrasound-assisted extraction (UAE), and enzyme-assisted extraction (EAE). SFE uses supercritical CO₂ as a solvent, minimizing the need for toxic chemicals and reducing waste. MAE utilizes microwave radiation to enhance extraction efficiency, cutting down on extraction time and solvent use. UAE employs ultrasonic waves to increase extraction yields and reduce processing time, while EAE leverages enzymes to selectively extract bioactive compounds without harsh chemicals. Each method's effectiveness, environmental impact, and economic feasibility are critically evaluated. The review also highlights recent advancements in these techniques, including the integration of nanomaterials and optimization strategies. By adopting green chemistry principles, the extraction processes can be more sustainable, economically viable, and less harmful to the environment. The findings suggest that while each green method has its advantages, combining techniques or refining existing methods can further enhance the efficiency and sustainability of bioactive compound extraction.